The Effect of Ownership Structure and Board Gender Diversity on Dividend Policy : (Kompas 100 Index Stocks, 2019-2023) - Salsabila Sonia; Ernie Hendrawaty; Nindytia Puspitasari Dalimunthe (International Forum of Researchers and Lecturers, 2025)
Decisions regarding dividend payment policy represent a key aspect of corporate governance, closely tied to the active involvement of board members. These decisions are often shaped by the firm's ownership structure. The growing presence of women in managerial roles further emphasizes their influence in strategic decision-making, including dividend-related choices. This study investigates the impact of board size, ownership structure, and female board representation on dividend policy among companies listed in the Kompas 100 index from 2019 to 2023, grounded in agency theory and corporate governance principles. Using multiple linear regression, the research analyzes the dividend payout ratio as the dependent variable, with independent variables including managerial, family, institutional, and government ownership, along with board size and female board representation. The findings reveal that board size, ownership structure, and female board membership collectively influence dividend policy. However, individually, ownership structure shows no significant impact, while both board size and female representation exhibit a significant positive effect on dividend policy, suggesting that larger boards and greater female participation contribute positively to dividend decisions.